‘Facing Uncharted Waters’: Challenges experienced by Occupational Therapy Students undertaking Role-emerging Placements - Clarke, Channine; Martin, Marion; Sadlo, Gaynor; de-Visser, Richard (International Journal of Practice-based Learning in Health and Social Care, 2015)
Role-emerging placements, which take place in settings where there are no on-site occupational therapy educators, are increasingly being used within occupational therapy curricula internationally. Although literature on such placements is increasing, little has explored the early stages and demands of such placements. Interpretative phenomenological analysis was used to gain an understanding of how five MSc pre-registration occupational therapy students experienced and ascribed meaning to their role-emerging placements. Interviews were carried out with the students within one month of their role-emerging placement. This article explores one of the themes that emerged from the study, ‘Thrown in’, that reflected the challenges students faced in the early days of their placement. Key findings revealed that students found the early stages of placement cognitively, emotionally and ontologically demanding. They felt temporarily lost, anxious and overwhelmed by their experience, which impacted on their sense of self. Recommendation is made that consideration is given to students’ ontological discomfort, or ‘sense of being’ on placement and pre-placement preparation.